Two new species of Atractus from Colombia (Reptilia, Squamata, Dipsadidae) - Köhler, Gunther; Kieckbusch, Max (Zootaxa, 2014)
We describe two new species of Atractus from Colombia: one from the Serrania de la Lindosa, south of San José de Guaviare in the province Guaviare, and another from Punta de Betin in the province Magdalena, close to the Caribbean coast. The first new species differs from all congeners by having a combination of 17 smooth dorsal scale rows; loreal present, approximately as long as high; temporals 1+2; seven supralabials; seven infralabials; five maxillary teeth; four gular scale rows; four pre-ventrals; 187 ventrals in single male; 29/31 subcaudals in single male; dorsum of body with longitudinal stripes; venter uniformly dark gray. The second new species differs from all congeners by having a combination of 17 smooth dorsal scale rows; loreal absent; temporals 1+2; seven supralabials; six or seven infralabials; eight maxillary teeth; three gular scale rows; three pre-ventrals; 146 ventrals in single male; 31/32 subcaudals in single male; dorsum of body and tail reddish brown with paired, occasionally slightly alternating lateral vertical cream blotches, approximately one dorsal scale broad, not contacting in vertebral region; venter cream with reddish brown blotches, forming two parallel series on anterior body and a checkered pattern on the rest of body.